Environmental management in ethanol and sugarcane plants in Brazil - Ribeiro, Silvio [UNESP]; Chiappetta Jabbour, Charbel Jose (Taylor & Francis Inc, 2012)
There has been much discussion on the importance of Brazilian ethanol in promoting a more sustainable society. However, there is a lack of analysis of whether sugarcane plants/factories that produce this ethanol are environmentally suitable. Thus, the objective of this study was to analyse stages of environmental management at four Brazilian ethanol-producing plants, examining the management practices adopted and the factors behind this adoption. The results indicate that (1) only one of the four plants is in the environmentally proactive stage; (2) all plants are adopting operational and organisational environmental management practices; (3) all plants have problems in communicating environmental management practices; and (4) the plant with the most advanced environmental management makes intense use of communication practices and is strongly oriented towards a more environmentally aware international market. This paper is an attempt to explain the complex relationship between the evolution of environmental management, environmental practices and motivation using a framework. The implications for society, plant directors and scholars are described, as well as the study's limitations.
Keywords: sustainable development; environmental management practices; sugarcane and ethanol-processing plants; Brazil